2021
DOI: 10.1111/ppc.12750
|View full text |Cite
|
Sign up to set email alerts
|

The effects of progressive muscle relaxation exercises on the anxiety and sleep quality of patients with COVID‐19: A randomized controlled study

Abstract: Purpose This study aimed to determine the effects of progressive muscle relaxation exercises on the anxiety and sleep quality of patients with coronavirus disease 2019 (COVID‐19). Materials and Methods This is an experimental study. Its data were collected in the infectious diseases clinic of a research hospital from May to August, 2020. This study was carried out with 67 COVID‐19 patients (33 in the experimental group and 34 in the control group). The data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 34 publications
3
64
0
1
Order By: Relevance
“…However, there was no significant difference in the number of patients who were able to perform the single-leg stance test among participants who did not receive ICU care(28). Similar results for anxiety were found in Özlü et al's RCT(16). They concluded that, after 5 days of progressive muscle relaxation, the anxiety scores of COVID-19 patients improved in the interven-tion group (State-Trait Anxiety Inventory (STAI) score pre: 62.33(8.33); post: 44.67 (5.41); p < 0.001).…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, there was no significant difference in the number of patients who were able to perform the single-leg stance test among participants who did not receive ICU care(28). Similar results for anxiety were found in Özlü et al's RCT(16). They concluded that, after 5 days of progressive muscle relaxation, the anxiety scores of COVID-19 patients improved in the interven-tion group (State-Trait Anxiety Inventory (STAI) score pre: 62.33(8.33); post: 44.67 (5.41); p < 0.001).…”
supporting
confidence: 69%
“…(15). Six studies included active COVID-19 patients, of which 2 studies were on patients admitted to the ICU (19,26), 2 studies were on patients admitted to other inpatient care units (16,24), and 2 studies included both (20,29). Five studies included recovered COVID-19 patients who were still receiving inpatient rehabilitation were assessed in 8 studies (15,17,18,19,22,24,26,29).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Systematic epidemic prevention programs, such as in-service training, human resources allocation, gathering sufficient protective equipment, and establishing a mental health team, could improve anxiety, depression levels, and sleep quality among battlefront staffs ( 30 ). Progressive muscle relaxation training could alleviate anxiety and improve sleep quality, and this training can be performed remotely and multiple times after one training session ( 31 ). During the outbreak, we advocate that medical institutions adopt systematic prevention programs and psychological interventions to alleviate anxiety and depression and improve sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the RCSQ score presented in the study results was only the posttest score between the two groups, in which the experimental group has a significantly better RCSQ post-test score. 15…”
Section: Resultsmentioning
confidence: 99%
“…In the results of the three studies, PMR was effective in improving anxiety symptoms and sleep quality in COVID-19 patients. [13][14][15]…”
Section: Reviewmentioning
confidence: 99%